1992
DOI: 10.1002/jsfa.2740600410
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different nitrogen and potassium fertilisation on the chemical flavour composition of kohlrabi (Brassica oleracea var gongylodes L)

Abstract: Abstract:The aims of this study were to investigate the influence of fertiliser treatments on the chemical flavour composition of kohlrabi (Brassica oleracea var gongylodes L). Increasing nitrogen and potassium supply resulted in variable amounts of isothiocyanates, organic cyanides, sulphides and aldehydes measured by headspace analysis. Therefore it could be suggested that the desirable flavour of kohlrabi is influenced by the level of fertilisation. The effect of applied potassium on flavour quality is less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
2

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 10 publications
4
13
2
Order By: Relevance
“…The maximum dry weight of knob (11.55%) was recorded from the K 3 (80 kg K ha -1 ) while the minimum dry weight of knob (9.46%) was found from K 0 (control) treatment (Table 1). Fischer (1992) found similar results in kohlrabi. The maximum marketable yield per plot (6.18 kg) was observed from the K 3 (80 kg K ha -1 ) treatment while the minimum marketable yield per plot (4.63 kg) was found from K 0 (control) treatment (Table 1).…”
Section: Effects Of Potassiumsupporting
confidence: 77%
“…The maximum dry weight of knob (11.55%) was recorded from the K 3 (80 kg K ha -1 ) while the minimum dry weight of knob (9.46%) was found from K 0 (control) treatment (Table 1). Fischer (1992) found similar results in kohlrabi. The maximum marketable yield per plot (6.18 kg) was observed from the K 3 (80 kg K ha -1 ) treatment while the minimum marketable yield per plot (4.63 kg) was found from K 0 (control) treatment (Table 1).…”
Section: Effects Of Potassiumsupporting
confidence: 77%
“…Hsu et al (2009) also found an increase in a single glucosinolate (sinigrin) in Brassica grown in pots with an organic soybean meal treatment compared with those in synthetic fertilizer. Brassica glucosinolate concentrations often decrease in response to increasing fertilizer or nitrogen supply (Fischer 1992;Chen et al 2004;Aires et al 2006;Schonhof et al 2007), but, with the exception of glucoiberin, we found no effect of fertilizer quantity on glucosinolate concentration. The differences in glucosinolate concentration found in the current study were probably constitutive rather than induced (Siemens & Mitchell-Olds 1998), as the dominant chewing herbivore (P. xylostella) was more abundant on the conventional plants, which had a lower concentration of glucosinolates.…”
Section: Discussioncontrasting
confidence: 55%
“…Probably, the increase in plant growth and N uptake in presence of the soil organisms affected the concentration of this secondary metabolite. Both positive (Gustine and Jung 1985;Werteker 1991;Hugentobler and Renwick 1995) and negative correlations (Wolfson 1982;Fischer 1992) between nitrogen availability and glucosinolate concentration have been documented. The second sulphur containing glucosinolate, glucoraphanin, was affected by an interaction between earthworms and nematodes.…”
Section: Discussionmentioning
confidence: 99%